2013
DOI: 10.31357/fesympo.v0i0.1534
|View full text |Cite
|
Sign up to set email alerts
|

A Preliminary Study on the Presence of-Heavy Metals in Aquatic Plants From a Freshwater Wetland at Kelaniya

Abstract: Aquatic plants are known for uptake of heavy metals from water and sediments. This very feature qualifies these plants as wastewater treatment agents. Capacity to absorb, heavy metals however, varies among plants.Three aquatic plants, Pistia stratiotes (floating), Limnocharis jlava (rooted) and Ipomoea aqualica (rooted plant with floating runners) from lriyawetiya wetland at Kelaniya were tested for the presence of copper, zinc, lead, nickel, cadmium, manganese, tin and chromium in the plant tissues.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2013
2013
2014
2014

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…Likewise Hg in sediment, at an average of 0.129 mg/kg, is less prominent than the level reported in two hydroelectric reservoirs in Quebec, Canada (0.15–0.49 mg/kg) [ 40 ]. Tin is found in elevated concentration in macroalgae and aquatic plants; according to Thompson et al [ 41 ], the bioaccumulation factor of Sn in these samples can be as high as 100 where Nirbadha et al [ 42 ] likewise revealed relatively large quantities of Sn in three aquatic plants in Kelaniya.…”
Section: Resultsmentioning
confidence: 99%
“…Likewise Hg in sediment, at an average of 0.129 mg/kg, is less prominent than the level reported in two hydroelectric reservoirs in Quebec, Canada (0.15–0.49 mg/kg) [ 40 ]. Tin is found in elevated concentration in macroalgae and aquatic plants; according to Thompson et al [ 41 ], the bioaccumulation factor of Sn in these samples can be as high as 100 where Nirbadha et al [ 42 ] likewise revealed relatively large quantities of Sn in three aquatic plants in Kelaniya.…”
Section: Resultsmentioning
confidence: 99%
“…Nirbadha et al . () also revealed that relatively large quantities of Sn were found in all three species. The highest Cr content was observed in L .…”
Section: Discussionmentioning
confidence: 76%
“…Their results showed that the heavy metals concentrations in the roots were generally higher than in the shoots. Nirbadha et al (2003) also revealed that relatively large quantities of Sn were found in all three species. The highest Cr content was observed in L. flava.…”
Section: Discussionmentioning
confidence: 83%
See 2 more Smart Citations